2023
DOI: 10.3390/ijms241210113
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mitochondrial Transplantation on Sepsis Depend on the Type of Cell from Which They Are Isolated

Abstract: Previously, we have shown that mitochondrial transplantation in the sepsis model has immune modulatory effects. The mitochondrial function could have different characteristics dependent on cell types. Here, we investigated whether the effects of mitochondrial transplantation on the sepsis model could be different depending on the cell type, from which mitochondria were isolated. We isolated mitochondria from L6 muscle cells, clone 9 liver cells and mesenchymal stem cells (MSC). We tested the effects of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, in situations of irreversible damage, mitochondrial transplantation could offer a novel and innovative strategy [10]. We previously showed that mitochondrial transplantation could have immune modulation effects in a sepsis model [13,19]. Anti-inflammatory, anti-apoptotic, and immune enhancing effects were revealed as potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, in situations of irreversible damage, mitochondrial transplantation could offer a novel and innovative strategy [10]. We previously showed that mitochondrial transplantation could have immune modulation effects in a sepsis model [13,19]. Anti-inflammatory, anti-apoptotic, and immune enhancing effects were revealed as potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%